Cytotoxic and Morphological Effects of Chrysanthemum Indicum Aqueous Extracts of Bud and Flower on Human Acute Promyelocytic Leukemia (APL) HL-60 Cell Lines in vitro. - Wan Nurfarahin, Wan Osman; Hudaa Zulfaa, Mohd Zainuddin; Nuriana Munirah, Hairul (Penerbit Universiti Sultan Zainal Abidin, 2020)
Chrysanthemum indicum (C.indicum) plants, also known as “bunga kekwa” in Malaysia has long history used in Chinese traditional herbal medicines, with anti-oxidants, anti‑inflammatory and anti-cancer properties. This study was to determine the anti-cancer activity of buds and flowers of C.indicum in aqueous extracts on human acute promyelocytic leukaemia cancer HL-60 cell lines. The powder of bud and flower were macerated in the sterile distilled water for 24 hr. The bud aqueous (BA) and flower aqueous (FA) extracts were concentrated under reduced pressure using rotary evaporator. The cells were treated at 12.5 µg/ml, 25 µg/ml, 50 µg/ml, 100 µg/ml, 200 µg/ml and 400 µg/ml and incubated for 24, 48 and 72 hr. The cellular morphology of HL-60 cells was observed by phase contrast microscopy while the cytotoxic activity was determined using MTT assay. BA and FA extracts showed significant reduction of HL-60 cell viability at 100, 200 and 400 µg/ml in all incubation period. Both extract also showed low cytotoxic activity against HL-60 cells (p <0.05) with IC50 value of 305 µg/ml and 320 µg/ml respectively at 24 hr, 310 µg/ml and 205 µg/ml respectively at 48 hr and 180 µg/ml and 170 µg/ml respectively at 72 hr. Even though BA and FA aqueous extracts were unable to kill the HL-60 cell lines effectively, the results still show some promising effect for C.indicum plant in treatment of blood cancer.